Quercetin-Induced Cell Death in Human Papillary Thyroid Cancer (B-CPAP) Cells - YALÇIN, AHMET SUHA; YILMAZ GÖLER, AYŞE MİNE; YILMAZ, BETÜL (HINDAWI LTD, 2016)
In this study, we have investigated the antiproliferative effect of quercetin on human papillary thyroid cancer cells and determined the apoptotic mechanisms underlying its actions. We have used different concentrations of quercetin to induce apoptosis and measured cell viability. Apoptosis and cell cycle analysis was determined by flow cytometry using Annexin V and propidium iodide. Finally, we have measured changes in caspase-3 and cleaved poly(ADP-ribose) polymerase (PARP) protein expression levels as hallmarks of apoptosis and Hsp90 protein expression level as a marker of proteasome activity in treated and control cells. Quercetin treatment of human papillary thyroid cancer cells resulted in decreased cell proliferation and increased rate of apoptosis by caspase activation. Furthermore, it was demonstrated that quercetin induces cancer cell apoptosis by downregulating the levels of Hsp90. In conclusion, we have shown that quercetin induces downregulation of Hsp90 expression that may be involved in the decrease of chymotrypsin-like proteasome activity which, in order, induces inhibition of growth and causes cell death in thyroid cancer cells. Thus, quercetin appears to be a promising candidate drug for Hsp90 downregulation and apoptosis of thyroid cancer cells.
Keywords: DIETARY FLAVONOIDS; APOPTOSIS; INHIBITION; POLYPHENOLS; BIOAVAILABILITY; PROLIFERATION; CHAPERONES; STRATEGIES; PATHWAYS; PROTEINS